Gonadal hormones modulate the HPA‐axis and the SNS in response to psychosocial stress. Issue 8 (9th May 2018) - Barel, Efrat; Abu‐Shkara, Randa; Colodner, Raul; Masalha, Refaat; Mahagna, Lila; Zemel, Or Chen; Cohen, Ami
Abstract: Exposure to stress activates both the hypothalamus‐pituitary‐adrenal (HPA) axis and the sympathetic nervous system (SNS). A growing body of research points to the contribution of sex hormones (testosterone, estrogen, and progesterone), the end products of the hypothalamus‐pituitary‐gonadal (HPG) axis, in modulating stress reactivity. The present study aimed at investigating the potential modulating role of sex hormones on HPA and SNS reactivity to psychosocial stress. The reactivity, induced by the Trier Social Stress Test, was analyzed by measuring the levels of cortisol and alpha‐amylase (markers for SNS activity) in four saliva samples each of 21 men and 37 women (17 not using oral contraceptives and in their luteal phase, and 20 women using oral contraceptives). In addition, basal sex hormones were sampled prior to the psychosocial stress exposure. Results revealed that controlling for testosterone, estrogen, and progesterone diminished the impact of stress on cortisol reactivity and on alpha‐amylase reactivity. Moreover, controlling for sex hormones also diminished the differential pattern of cortisol reactivity in each experimental group among responders. Furthermore, correlation analyses revealed differences between groups in the association between sex hormones and alpha‐amylase. The present findings indicate a modulatory role for sex hormones in HPA and SNS reactivity and emphasize the need for control of sex hormone fluctuations when examining cortisol and alpha‐amylase reactivity to stress.